Influence of ground motion spatial variation, site condition and SSI on the required separation distances of bridge structures to avoid seismic pounding. - Bi, Kaiming
It is commonly understood that earthquake ground excitations at multiple supports of large dimensional structures are not the same. These ground motion spatial variations may significantly influence the structural responses. Similarly, the interaction between the foundation and the surrounding soil during earthquake shaking also affects the dynamic response of the structure. Most previous studies on ground motion spatial variation effects on structural responses neglected soil-structure interaction (SSI) effect. This paper studies the combined effects of ground motion spatial variation, local site amplification and SSI on bridge responses, and estimates the required separation distances that modular expansion joints must provide to avoid seismic pounding. It is an extension of a previous study in which combined ground motion spatial variation and local site amplification effects on bridge responses were investigated. The present paper focuses on the simultaneous effect of SSI and ground motion spatial variation on structural responses. The soil surrounding the pile foundation is modelled by frequency-dependent springs and dashpots in the horizontal and rotational directions. The peak structural responses are estimated by using the standard random variation method. The minimum total gap between two adjacent bridge decks or between bridge deck and adjacent abutment to prevent seismic pounding is estimated. Numerical results show that SSI significantly affects the structural responses, and cannot be neglected.
Keywords: Required separation distance; SSI; Site effect; Ground motion spatial variation; MEJ